Android-Based E-Booklet Development to Train Students’ Critical Thinking And Attitude of Caring for Environment (Journal of Innovative Science Education, 2021)
Biology subjects in high school learn everything about life. In this case it involves skills and reasoning. This study aims to analyze the validity, effectiveness, practicality, and characteristics of android-based e-booklets. This research is a research and development or R&D. The development in this study adopted a 4-D model which included four stages namely define, design, develop, dissemination. The results of the study on the validity test showed that the material experts obtained a value of 92.14% with a very good category. Based on the results of the validation of media experts obtained a value with a percentage of 86.29% in the very good category. The results of the research on the effectiveness of android-based e-booklet are 1) classical completeness ≥ 80%, 2) N-Gain test results are different and better (has increased). Cognitive learning outcomes (students' critical thinking) showed that the percentage of students’ classical completeness was 88.27%, the N-Gain Test was in the high (53%), moderate (45%), low (2%) category. Based on the analysis of affective and psychomotor competencies with very good criteria. The results of research on students’ attitudes of caring for environment showed that the percentage of students' scores was 82% with an excellent category. Based on the effectiveness analysis it can be concluded that the android-based e-booklet is effectively applied in biodiversity subject. In the analysis of the results of the practicality of the android-based e-booklet media showed a very good response from teachers and students. The characteristics of an android-based e-booklet consist of a cover, a menu display consisting of preface, KI and KD, material, and evaluation questions.